Instrumentation applied in agricultural machines: systematic literature review (Research, Society and Development, 2021)
In order to analyze the publications on the use of instrumentation in agriculture, the objective of this paper is to present a set of works published between 2017 and 2021 on the subject so that an analysis of the technologies developed during this period can be carried out. For this, a search was carried out in the IEEE, Science Direct and Scopus databases, where 1490 published articles were found using a search string to select papers considering theme, year of publication. In view of this result, the Start software was used to apply selection criteria to choose the articles to be used in the review. After performing all the steps of selection of works in the software, the result was 33 papers carrying out the Systematic Review. Of the 33 articles, the work methods and the result obtained by the author are presented, thus enabling an analysis of the technologies researched during the study period.